Model concepts to support the improvement of students' skills in learning tasks - Kemala Jeumpa; Rumila Harahap (Jurnal Pendidikan Vokasi, 2023)
This article aims to design a concept model that can support learning to improve students' ability in learning tasks to deal with problems that exist in the real world. Based on KKNI (Indonesian National Qualification Framework), there are six tasks in learning, namely routine tasks, critical book reports, critical journal reports, idea engineering (scientific or creative writing), mini research, and projects. Therefore, the learning process must be able to increase student learning motivation. In addition, it must also develop their competencies and skills to think critically, have high creativity, be able to work together in teams, be disciplined, be responsible, and be able to create frameworks and solve problems in life and the environment. Therefore, it is necessary to develop a learning model that is in accordance with these objectives. In this case, it is a learning model designed to encourage students to learn and practice, so that they are skilled in responding to problems based on their experience in learning. The approach in this development research was carried out using the ADDIE model. The design concept of this development model is done by combining a project-based learning model with six tasks based on KKNI (Indonesian National Qualification Framework). The results of the design concept of this development model consist of seven syntax stages, namely: material explanation, material review and formulation of problem formulation, study and review of book and journal literature, idea engineering (scientific or creative writing), mini research, project design and implementation, and presentation and evaluation.